Design of a low-power 10-bit 12-MS/s asynchronous SAR ADC - Campos, Arthur Lombardi (2020)
This work presents the design of a low-power 10-bit 12-MS/s Successive Approximation Register (SAR) Analog-to-Digital Converter (ADC) in 65-nm technology, suitable for IEEE 802.15.4g standard frontend receivers (low data rate and power consumption smart utility networks). By using the differential implementation with a pair of bootstrapped switches, the input signal is sampled with low distortion. The asynchronous implemen-tation of the SAR circuit leads to an increased system flexibility because only a single clock source is required. To support the merged capacitor switching scheme (MCS), a three-level switch circuit was designed for the capacitor array. The simulated circuit achieved a 9.65 ENOB with 151.4 μW of power consumption at 12 MS/s, leading to a FOM of 15.8 fJ/Conversion-step. Simulations have also shown that the ADC is efficient for sampling frequencies ranging from 10 kS/s up to 12 MS/s, extending its usability to low sampling frequency circuits.